Detemination of Urea Using Fia-Cl System - Ismail, Wshyar A.; Faizullah, Azad T. (Science Journal of University of Zakho, 2013)
In this work a sensitive chemiluminescence (CL) method for the determination of urea was investigated using a reaction between hypobromite and urea in basic medium. The hypobromite (OBr-) was generated by on-line reaction of Br2 with KOH, where Br2 was previously generated by another on-line reaction of KBrO3 with KBr in acidic medium. The proposed method was applied successfully for the determination of urea in human blood serum after elimination of interferences by several methods. The important one was the introduction of a dialysis unit into the FIA-CL system to eliminate proteins interfering effects by placing it in the sample stream with some modification in the arrangement of FIA-CL system. The linear range of the method in the absence of dialysis unit, where the interference effects were solved by dilution, was 5.0 x 10-7 – 1.0 x 10-2 mol/l urea with a correlation coefficient of 0.9958, a detection limit 8.0 x 10-8 mol/l urea and sample throughput of 180 sample/h. In the presence of dialysis unit, however, these were 1.25 x 10-5 – 0.26 mol/l urea, 0.9987, 2.5 x 10-6mol/l urea and 35 sample/h.
Keywords: Urea; Flow injection; Chemiluminescence; Serum